Views and attitudes of university students in Upper Egypt towards youth health centers - Mohamed M. Abd El-Mawgod; Shimaa A. Elghazally; Heba M. Mohammed; Mariam Roshdy Elkayat; Doaa M. M. Osman (SpringerOpen, 2020)
Abstract Background A healthy youth is considered the major human resource for any country development. They are suffering from unmet health needs. Considering these needs and their attitude towards the use of youth health center (YHC) services would help to improve both the quality and quantity of these services. Objectives To identify the students' perceived health needs and their attitude towards use of the YHCs in Assiut University campus, Upper Egypt a cross-sectional study was conducted among 305 randomly selected university students. Data were collected using an interviewer-administered questionnaire. Results The majority of the students (80%) said that youth have special health needs. The most reported needs were psychological support, health education on different topics including reproductive health and sexually transmitted diseases, and nutritional services respectively. There was a high perception among surveyed students (71.5%) that the existing health services are inadequate for meeting their needs. Counseling, laboratory services, and premarital examination were the most frequently reported services mentioned by youth to be offered in YHCs. The majority (78.1%) preferred the health provider to be of the same sex. Despite the prevailing conservative culture in Upper Egypt, the students had positive attitude towards availability of sexual and reproductive information and establishment of a YHC in the university campus. A low awareness rate (15.1%) about the already existing YHC in university campus was revealed. Conclusion University students perceived that there are unmet needs for youth-specialized services, mainly for providing sexual and reproductive information, and establishment of an on-campus YHC. The study provides important information for policymakers about the perspectives of youth which should be taken into consideration when new YHC are planned and implemented.